2015
DOI: 10.1088/1674-1056/24/7/077304
|View full text |Cite
|
Sign up to set email alerts
|

Energy distribution extraction of negative charges responsible for positive bias temperature instability

Abstract: A new method is proposed to extract the energy distribution of negative charges, which results from electron trapping by traps in the gate stack of nMOSFET during positive bias temperature instability (PBTI) stress based on the recovery measurement. In our case, the extracted energy distribution of negative charges shows an obvious dependence on energy, and the energy level of the largest energy density of negative charges is 0.01 eV above the conduction band of silicon. The charge energy distribution below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In order to obtain the quantity and distribution of N OX in HK bulk, a new method is proposed, as described in Fig.2, based on PBTI recovery characteristics [12,13]. Figure5(a)shows that the larger trap density of the device with thinner capping TiN under both 90 • C and 160 • C. Figure5(b)shows the energy profile extraction for traps by using ramp recovery stress, which is described in detail below,[14] similar to that in our previous work [15]. (i) V th shift after completing discharge under each V discharge is converted into the effective charge density, i.e., N OX and plotted against V discharge , where N OX = ∆V th ε 0 ε r /dq, with ∆V th = V th (end of each discharge)-V th0 (T stress = 0);(ii) The next task is to convert V discharge into the energy level of E C , i.e., (E T − E C ), by the oxide band structure, the same as that of our previous work,[15] where E T − E C = q •V OX and V g = V OX +V S +V ms , with E T being the trap energy level and E C the conduction band of substrate silicon, and V S the surface potential drop;…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…In order to obtain the quantity and distribution of N OX in HK bulk, a new method is proposed, as described in Fig.2, based on PBTI recovery characteristics [12,13]. Figure5(a)shows that the larger trap density of the device with thinner capping TiN under both 90 • C and 160 • C. Figure5(b)shows the energy profile extraction for traps by using ramp recovery stress, which is described in detail below,[14] similar to that in our previous work [15]. (i) V th shift after completing discharge under each V discharge is converted into the effective charge density, i.e., N OX and plotted against V discharge , where N OX = ∆V th ε 0 ε r /dq, with ∆V th = V th (end of each discharge)-V th0 (T stress = 0);(ii) The next task is to convert V discharge into the energy level of E C , i.e., (E T − E C ), by the oxide band structure, the same as that of our previous work,[15] where E T − E C = q •V OX and V g = V OX +V S +V ms , with E T being the trap energy level and E C the conduction band of substrate silicon, and V S the surface potential drop;…”
mentioning
confidence: 65%
“…[12,13] Figure 5(a) shows that the larger trap density of the device with thinner capping TiN under both 90 • C and 160 • C. Figure 5(b) shows the energy profile extraction for traps by using ramp recovery stress, which is described in detail below, [14] similar to that in our previous work. [15] (i) V th shift after completing discharge under each V discharge is converted into the effective charge density, i.e., N OX and plotted against V discharge , where N OX = ∆V th ε 0 ε r /dq, with ∆V th = V th (end of each discharge)-V th0 (T stress = 0);…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determined E A values of both samples were less than 0.1 eV, indicating that the PBTI degradation was dominated by the pre-existing traps instead of the generated traps [6]. Furthermore, the energy distribution of the traps in the HfO 2 layer was also extracted from the recovery characteristics (not shown here) [7], as presented in Figure 1(d). The trap density peaks for the two samples were located near the edge of the conduction band (E c ).…”
Section: As Depicted Inmentioning
confidence: 99%
“…It is concluded that the interface trap degradation is severe under such a high stress condition, which is different from PBTI characteristic in our previous work. [15,16] The charge pumping method is used to directly measure interface trap density in fresh devices. In charge pumping measurement, the pulse amplitude is constant and base level voltage sweep is applied.…”
Section: Interface Trap Degradationmentioning
confidence: 99%